ASSERTIVE SPEECH ACTS IN MATA NAJWA PROGRAM OF EPISODE GARE-GARE CORONA - izar, Julisah; Nasution, Muhammad Muslim; Ratnasari, Mie (Universitas Pamulang, 2020)
The main objective of this study is to find out the types and functions of assertive speech acts that appear in Mata Najwa program in episode Gara-Gara Corona. The method used in this study is a qualitative descriptive method by analyzing and explaining the data obtained. The data in this study were speech segments in the Mata Najwa episode Gara-Gara Corona which indicate assertive speech acts. The data source in this study is the video of the program entitled